AI-POWERED HEART FAILURE PREDICTION AND MONITORING TOOLS - Roman Khan; Arbaz Haider Khan; Hira Zainab; Hafiz Khawar Hussain (CV. Shofanah Media Berkah, 2024)
Recently, a chronic and severe form of cardiovascular diseases – heart failure (HF) – became preventable with the aid of artificial intelligence (AI). In this article, we explore the multiple ways in which AI is employed to enhance the care of patients with heart failure: remote real-time supervision systems, individualized interventions, risk assessment models. AI’s ability to review massive amounts of data from Wearables, electronic health, and record checking tools may aid heart failure early detection, risk elevation, and preventive treatments. This enhances the patients’ quality of life, and also reduces the client’s expenditure on healthcare. Several challenges remain relating to: AI availability and data quality; algorithm explain ability; legal and regulatory aspects; and patient engagement, even if there are positive preliminary signs for the broad development of AI-based solutions in the health field. Even bigger promises for the improvement of precision and individualized heart failure therapy are seen in future developments of AI through application of big data, genomics, and remote touchscreen monitors. The work on the improvement of the explainable AI models and expanded international cooperation will also help solve these problems and enhance the efficiency as well as equity of heart failure treatment. With rapid advancements in Artificial Intelligence, it is expected that the care of patients with heart failure will be transformed, both in terms of time, efficiency, and individual patient needs.